Perancangan Aplikasi Elearning Berbasis Web Pada Sman 17 Muaro Jambi - Sirait, Gusnaldi Triardo; M Riza Pahlevi; Eni Rohaini (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2024)
The teaching and learning process at SMAN 17 Muaro Jambi currently still uses traditional learning methods where learning involves meet face-to-face interaction in the classroom at scheduled times, where the teacher delivers material and students take notes while doing the exercises given. In order to design an e-learning application, the author collected data through interviews, direct observation and analysis document. The result of this research is the development of an e-learning application system that uses a web-based platform that makes it easier for teachers to provide material and assignments in the teaching process and also helps students obtain material, so that students can learn easily and efficiently. It is hoped that the application that has been created will be useful for teachers and students at SMAN 17 Muaro Jambi.